Effects of Growth Hormone on Adult Human Gonads: Action on Reproduction and Sexual Function. (7th April 2023) - Zhou, Xin-Yi; Ma, Jia-Ni; Shen, Ya-Yin; Xie, Xue-Rui; Ren, Wei
Abstract : Growth hormone (GH), which is commonly considered to be a promoter of growth and development, has direct and indirect effects on adult gonads that influence reproduction and sexual function of humans and nonhumans. GH receptors are expressed in adult gonads in some species including humans. For males, GH can improve the sensitivity of gonadotropins, contribute to testicular steroidogenesis, influence spermatogenesis possibly, and regulate erectile function. For females, GH can modulate ovarian steroidogenesis and ovarian angiogenesis, promote the development of ovarian cells, enhance the metabolism and proliferation of endometrial cells, and ameliorate female sexual function. Insulin-like growth factor-1 (IGF-1) is the main mediator of GH. In vivo, a number of the physiological effects of GH are mediated by GH-induced hepatic IGF-1 and local IGF-1. In this review, we highlight the roles of GH and IGF-1 in adult human gonads, clarify potential mechanisms, and explore the efficacy and the risk of GH supplementation in associated deficiency and assisted reproductive technologies. Besides, the effects of excess GH on adult human gonads are discussed as well.